Call for Papers: Beyond COVID - JIPE Journal of Innovation in Polytechnic Education (Journal of Innovation in Polytechnic Education)
How must we move forward? The COVID-19 pandemic is a multidimensional crisis that has brought to the surface deeply-embedded challenges in industry, academia, and the socio-political realm. To move beyond COVID is to recognize the complexity, depth and interdisciplinarity of solutions that will improve social, political, scientific and technological outcomes globally. Expressions of interest are invited for a Special Issue of the Journal of Innovation in Polytechnic Education exploring the topic of “Beyond COVID.” Authors are invited to submit a 250 to 500 word expression of interest, describing a paper they would like to contribute to the Special Issue. Proposed contributions could take the form of empirical papers, review papers, brief reports, or case studies.  See the PDF for all details.